(untitled) (Journal of Bio-Science, 2023)
Dendrobium is a sympodial, epiphytic orchid that belongs to the family of Orchidaceae. Bangladesh has a total of 188 different species under 78 genera of this tribe. Among them, there are 27 species of Dendrobium. Considering the potential value, the 16 species of Dendrobium are especially highlighted for herbal, horticultural, and ornamental purposes. They are also valuable for flowering as pot plants or hanging baskets. Dendrobium orchids are highly important in economically, socially, culturally, and as medicinal orchids. The basic needs of humans, the morphological characteristics of these orchids, such as the shape of pseudobulb, leaf, variation of inflorescence, floral characteristics, and their biodiversity evaluation in Bangladesh, are very important, and have been taken up for the present study. Besides these, ruthless collection by people who are thirsty for beauty has made the species endangered. On the other hand, the species has lost its habitat due to the removal of large trees. So, this research program has been conducted to save these valuable species from extinction. In addition, by studying their morphology, scientists and researchers gain insights into the evolutionary adaptations, reproductive strategies, and ecological interactions of orchids. For the present study exist and endangered Dendrobium about 2-3 years old and flower bearing matured plants were studied for development of morphological characterization of these orchids were flourished. J. Bio-Sci. 30(2): 47-57, 2022